A Quality Model Based on Lean Service Quality Philosophy and the PMBOK to Reduce Non-compliant Products from a Retail Store in Peru - Ruiz-Ocampo, D. (2023)
Today, the importance of maintaining quality standards in any business is fundamental to the success of the business, so having engineering tools helps a lot to integrate optimal quality into products and services. For its part, the retail store model provides great support to the commercial sector, but it presents many problems when it comes to maintaining ideal quality standards due to the versatility of its processes and products. This article seeks to establish a model that allows retailers to adapt to the use of Lean tools that improve the quality of service, reduce waste and increase the effectiveness of work. For this purpose, quality tools are integrated and the PMBOK guideline is used as a guide in a convenience store, also counting on the support of the organization for the validation of the proposal.